Infrabel: a path to disability inclusion: identified drivers and barriers - De Vreese, Anne-Lore (2019)
The unemployment rate of PWD (people with disabilities) is nearly double the rate of people without disabilities. Research shows that organizations who hire PWD can see many benefits such as decreased turn-over, absenteeism, improved rates of innovation and increased revenues. Yet employers struggle with attracting and retaining this diversity group. This study aims to determine the drivers and barriers for integration of PWD in a Belgian public organization and presents an implementation plan to improve this integration. Data analysis uses qualitative and quantitative data from employees across different hierarchy levels. The results conclude that the main drivers that will foster this integration are the organizational change to human-centered culture, open culture, and empowering management style. The main identified barriers are lacking awareness and knowledge about disability, stereotypes regarding skills of PWD and organization’s lack of flexibility. Seven interventions are proposed through Lewin’s model of change.